Rorty Tentang Kebenaran dan Pendasaran Pengetahuan - Sungeb Wiranggaleng (ILMU USHULUDDIN, 2013)
This article describes Rorty’s thought on truth and justification. According to Rorty, the established truth within the philosophical history is built on false assumption of knowledge, i.e. knowledge as relation between subject, which represents, and object which is represented—in which he calls as representationalism. For him, the theory of correspondence and coherence just stresses on one of the two aspects; subject (scheme or language) in the case of coherence, and object (world or fact) for correspondence. Through criticism for representationalism, Rorty tries to go beyond both theories and their metaphysic. Rorty’s critiques start with claim that knowledge is social practices; inter-relation between man and man, not transaction between man and objects. From here, Rorty concludes that knowledge’s rationality and objectivity are not decided by objects, but thought’s inter-change in certain social context. Rorty’s view on knowledge’s sociability has succeeded to show such false assumptions on knowledge.